Eight Skills of Islamic Religious Education Teachers in Improving Student Learning Outcomes in Junior High School - Cici Nopriza; Feni Yulianti; Samiullah Adel; Hendra Susanti (International Journal of Multidisciplinary Research of Higher Education, 2021)
Teaching skills are an aspect that must be owned by a teacher to achieve success in learning, therefore teachers must have a high ability in learning. In fact, this study aims to describe the teaching skills of Islamic religious education teachers in improving student learning outcomes at Madrasah Tsanawiyah. In addition, to describe the actions of Islamic Religious Education teachers in improving student learning outcomes at Madrasah Tsanawiyah. This study uses a qualitative method with an approach case study, Research data were taken from thirty-six informants, consisting of school principals, teachers, and students by means of individual and group interviews. To strengthen the interview data the author also made direct observations of teachers and students. All interview and observation data were analyzed using Analysis Interactive the Milles & Hubberman model. The results of this study found eight teacher activities in teaching. The teaching skills of Islamic Religious Education teachers at Madrasah Tsanawiyah include i) opening lesson skills, ii) closing lesson skills, iii) explaining skills, iv) questioning skills, v) reinforcement skills, vi) variation skills, vii) small group discussion guiding skills, and viii) class management skills. This research has succeeded in uncovering eight teacher skills in teaching so as to improve student learning outcomes.